2023
DOI: 10.1108/ci-06-2022-0148
|View full text |Cite
|
Sign up to set email alerts
|

Towards closing the housing gap in the UK: exploration of the influencing factors and the way forward

Abstract: Purpose Housing provides constructed space for human activities. Literature indicates that housing impacts wealth, education attainment and health outcomes, among others. Because of its contributions to society, it is essential to develop and implement strategies that address the housing shortage experienced in most cities across the globe. This study aims to unpack the factors affecting housing production in the UK and chart the way forward. Design/methodology/approach In addressing this study's aim, an int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…For instance, LOS can be used to identify the best area to locate a crane for unloading precast components being delivered to a confined site in an urban area. [9] highlighted that integration of LOS would add value to the process of housing delivery. Additionally, the study identified several factors which will support the use of LOS in housing delivery, as shown in Figure 2.…”
Section: Lean Offsite and Simulation (Los)mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, LOS can be used to identify the best area to locate a crane for unloading precast components being delivered to a confined site in an urban area. [9] highlighted that integration of LOS would add value to the process of housing delivery. Additionally, the study identified several factors which will support the use of LOS in housing delivery, as shown in Figure 2.…”
Section: Lean Offsite and Simulation (Los)mentioning
confidence: 99%
“…Additionally, Olanrewaju et al (2018) [7] and Ritson (2023) [8] pointed out that the housing construction projects in the UK are encouraged to implement energy efficient and sustainable construction methods to achieve the Net Zero carbon targets by 2050. Furthermore, Daniel et al (2022) [9] highlighted that supply chain management (SCM), issues related to the skills and operations, land matters, opportunistic behaviour, and demand and supply are the main factors which are influencing housing production in the UK construction industry. The limitations of traditional construction methods have been identified as the reason for widening the demand and supply gap of housing delivery in the UK [10].…”
Section: Introductionmentioning
confidence: 99%
“…Until 2030, there is a need to build 96,150 residential units every day. As a result, in developing countries, bad governance has limited access to suitable housing [12]. According to a United Nations study, 50% of the world's population currently lives in cities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Qualitative data collection and analysis Industrialized building systems [12] Analysis of the housing shortage strategies…”
Section: Proffering Possible Policy Solutions For Housingmentioning
confidence: 99%